Expanding digital competence of students: activities of the center of digital skills of Osh state university (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article is devoted to the relevant problem of training students in the context of the implementation of the digitalization process in the field of education. Research methods: analysis of scientific and methodological literature, program documents, observation, personal participation in the activities of the Digital Skills Center. The positive and negative manifestations of the process of digitalization of education, possible areas of application of digital technologies in the Kyrgyz Republic are explored. Particular attention is paid to summarizing activities of the Center for Digital Skills, as one of the aspects of the digital activities of the Osh State University: the history of the creation of the DSC, the activities carried out on its basis, and the results of activities are described. Recommendations are given for the development of digital competence of students.
Keywords: Center for Digital Skills; education; student; volunteering; digital competencies